Dietary Resistant Starch From Potato Regulates Bone Mass by Modulating Gut Microbiota and Concomitant Short-Chain Fatty Acids Production in Meat Ducks - Zhang, Huaiyong; Qin, Simeng; Zhu, Yao; Zhang, Xiangli; Du, Pengfei; Huang, Yanqun; Michiels, Joris; Zeng, Quifeng; Chen, Wen (Frontiers in Nutrition, 2022)
Gut microbiota interfered using prebiotics may improve bone mass and alleviate the onset of bone problems. This study aimed to investigate the beneficial effect of resistant starch from raw potato starch (RPS) on bone health in meat ducks. Response to dietary graded level of RPS supplementation, both tibia strength and ash taken out linear and quadratic increase, and positively correlated with increased propionate and butyrate levels in cecal content. Moreover, further outcomes of gut microbiota and micro-CT analysis showed the beneficial effect of RPS on bone mass might be associated with higher Firmicutes proportion and the production of short chain fatty acids (SCFAs) in cecum. Consistent with improving bone mass, SCFAs promoted phosphorus absorption, decreased the digestive tract pH, and enhanced intestinal integrity, which decreased the expression of proinflammatory genes in both gut and bone marrow, and consequently depressed osteoclastic bone resorption mediated by inflammatory cytokines. These findings highlight the importance of “gut-bone” axis and provided a new insight into the effect of prebiotics on bone health.